Temporary right ventricular circulatory support following right ventricular infarction: results of a groin-free approach - Kremer, Jamila; Farag, Mina; Brcic, Andreas; Zubarevich, Alina; Schamroth, Joel; Kreußer, Michael; Karck, Matthias; Ruhparwar, Arjang; Schmack, Bastian (ESC heart failure, 2020)
Aims Acute right heart failure (RHF) is a severe complication of right ventricular infarction. The management of acute RHF poses a number of challenges, such as providing haemodynamic support. Temporary circulatory support (TCS) may be required upon failing medical therapy. The ProtekDuo® dual lumen cannula provides a minimally invasive option for (TCS) through a groin-free internal jugular vein approach. We present the largest patient series to date using the ProtekDuo® cannula as temporary right ventricular assist device (t-RVAD) in RHF after acute myocardial infarction (MI). Methods and results From July 2016 to November 2019, 10 patients underwent t-RVAD implantation for RHF following acute MI. Transthoracic and transoesophageal echocardiography were performed in all patients to assess cardiac function, with a particular focus on RV function. Cumulative 30-day survival was 60%. Mean TAPSE was 6.4 ± 3.1 mm, mean fractional area change was 12.1 ± 4.2%, and mean right ventricular end diastolic area was 19.8 ± 2.7 cm2. Mean implantation time was 32.8 ± 8.3 min. Mean interval after first cardiac intervention was 4.6 ± 5.8 days. Mean t-RVAD time was 10.0 ± 7.4 days with a significant reduction in central venous pressure 19.3 ± 2.7 vs. 8.2 ± 2.6 mmHg, P < 0.001 and a significant increase in central venous saturation 52.8 ± 15.6 vs. 80.0 ± 6.0%, P < 0.001. Mean intensive care unit stay was 18.6 ± 12.2 days. Four patients were weaned from TCS. Two patients were bridged to a long-term paracorporeal RVAD. There were no t-RVAD associated complications. Causes of death (n = 4) were multiorgan failure, electromechanical dissociation, and haemorrhagic stroke. Mean follow-up time was 96.0 ± 107.6 days. No independent predictors of mortality were identified in univariate analysis. Conclusions We show that groin-free, percutaneous implantation of the ProtekDuo® cannula is a feasible and safe tool for TCS in acute RHF post-MI. This approach provides the advantages of percutaneous implantation including complete mobilization and non-surgical bedside explantation, as well as the option for adding an oxygenator to the t-RVAD circuit.
Gesehen am 08.09.2021